2014
DOI: 10.1037/a0037119
|View full text |Cite
|
Sign up to set email alerts
|

Do students’ topic interest and tutors’ instructional style matter in problem-based learning?

Abstract: Two studies investigated the importance of initial topic interest (i.e., expectation of interest) and tutors’ autonomy-supportive or controlling instructional styles for students’ motivation and performance in problem-based learning (PBL). In Study 1 (N = 93, a lab experiment), each student participated in a simulated group discussion in which tutor instructions were manipulated to be autonomy supportive, internally controlling, or externally controlling. Controlling tutor instructions led to higher controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 65 publications
1
10
1
2
Order By: Relevance
“…This conclusion also fits with past educational research demonstrating that students' particular goals will moderate the effects of different motivational strategies (Boekaerts & Corno, 2005). For example, correlational research finds that when students are less self-motivated, they are more sensitive to teachers who behave in Running head: STUDYING AND SOCIAL NORMS controlling ways (Soenens et al, 2012), students who are interested in a topic receive more benefit from instruction that supports autonomy than students who have less interest (Wijnia et al, 2014), and extrinsically-motivated students are more likely to exhibit increased participation during gamified learning activities (Buckley & Doyle, 2014). The current study provides more direct experimental evidence that efforts to improve student behavior may have different mileages, depending on whether the motivational strategy complements the student's goals for engaging in learning activities.…”
Section: Discussionsupporting
confidence: 83%
“…This conclusion also fits with past educational research demonstrating that students' particular goals will moderate the effects of different motivational strategies (Boekaerts & Corno, 2005). For example, correlational research finds that when students are less self-motivated, they are more sensitive to teachers who behave in Running head: STUDYING AND SOCIAL NORMS controlling ways (Soenens et al, 2012), students who are interested in a topic receive more benefit from instruction that supports autonomy than students who have less interest (Wijnia et al, 2014), and extrinsically-motivated students are more likely to exhibit increased participation during gamified learning activities (Buckley & Doyle, 2014). The current study provides more direct experimental evidence that efforts to improve student behavior may have different mileages, depending on whether the motivational strategy complements the student's goals for engaging in learning activities.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, they considered that their mid-term meeting with the supervisor was a major catalyst for sharing in the group the references and data that had been collected by each member. This is not consistent with the findings of Wijnia et al (2014). Indeed, by studying the joint effects of students' interest and tutor's instructional style on motivation and performance in a PBL environment, these authors demonstrated the major importance of students' initial topic interest for subsequent performance in PBL whereas tutor-provided autonomy support did not improve autonomous motivation and performance.…”
Section: Learning Outcomes Satisfaction Of Students and Discussion contrasting
confidence: 50%
“…Sorbal (1994) investigated the role of peer-tutoring on perceptions of meaningfulness and interestingness of the learning process. Other studies have examined the role of tutors’ instructional styles or characteristics such as subject-matter expertise on students’ autonomous motivation or situational interest (Rotgans and Schmidt 2011a; Wijnia et al 2014), or the role of having a free choice of literature resources to study (Wijnia et al 2015). Noordzij and Wijnia (accepted) examined effects of problem quality on autonomous motivation and found that problems that are perceived as familiar, problems that result in the intended learning issues, and problems that promote critical reasoning, increase the level of interest in the problem and can in turn affect autonomous motivation.…”
Section: The Origins Of Motivation Discourse In Pblmentioning
confidence: 99%